Upaya Preventif Pemimpin Pendidikan Dalam Menekan Kasus Kekerasan Seksual Serta Peranan Permendikbud Nomor 30 Tahun 2021 - Muh. Bachtiar Aziz (JURNAL MAPPESONA, 2023)
This study aims to find out how the efforts of educational leaders in suppressing the number of cases of sexual violence in Higher Education are and also to find out how the role of Minister of Education and Culture Number 30 of 2021 in eradicating perpetrators of sexual violence is. The method used in this research is a qualitative method. And using data collection techniques with interview methods, questionnaire methods, and documentation methods. The results of this study are the educational leaders at IAIN Bone, especially the Tarbiyah Faculty, have made various efforts to prevent and minimize the occurrence of sexual violence in Higher Education. The policies that have been set are certainly in line with the vision and mission of the institution, making it easier for leaders to implement them. In addition, Permendikbud Number 30 of 2021 concerning the prevention of sexual violence in universities also plays an important role in reducing the number of cases of sexual violence.